Health information : informative guidance for the users / Ahmad Nur Azam Ahmad Ridzuan and Nurul Nabihah Mohd Shamsul - Ahmad Ridzuan, Ahmad Nur Azam; Mohd Shamsul, Nurul Nabihah (Universiti Teknologi MARA, Perak, 2019)
People can search any information in internet through platform such as Google search, Bing and many more. The health information technology made patient become the producer of their own health because it enables them to access their health information anywhere. Furthermore, there are many people search their medical information on the internet not only for themselves but sometimes also for their family members or friends. There are thousands of medical websites and some provide health information which are may or may not up to date and reliable. Therefore, this study attempts to explore on how to choose the reliable website especially those who interested on looking their health information. People including patients and consumers need to be noted where there are pros and cons of the health information that available on web. Choosing the reliable websites is the first step in gathering online health information. Next, people must get to know the person who wrote the information and the reviews. Besides, the health information must be written or reviewed by healthcare professionals. Many sources can be used by internet’s user to seek on health information which not only come from the internet but also on printed sources such as magazine and newspapers. Electronic health record (EHR) is now been used widely in order to record patient information in online basis as well as one of tools whereby it is deliberately used by users on looking into their health condition.